Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. Evaluating the Performance of Secondary Schools in the Gaza Strip in Light of the Balanced Scorecard and Its Relationship to Institutional Excellence: The Mediating Role of Organizational Commitment Dr. Mohammed Ibrahim Abu Borhom, Prof. Suleiman Hussein Al-Muzain 2. Ways to improve the performance of students in the Kingdom of Saudi Arabia in the results of international tests (PISA) from the point of view of educational supervisors Ms. Afaf Othman Al-Subhi, Ms. Wafiah Othman Al-Subhi, Prof. Abdullah Ali Al-Tamam 3. The reality of distributed leadership practice among middle school principals in Makkah Al-Mukarramah from the female teachers’ point of view Ms. Ghada Mohammed Al-Lehyani ,Dr. Aishah Hamd Al-Ghaidi 4. Development of Foresight Leadership Skills for Female Principals of Public Schools in Jeddah from Their Perspective Ms. Haneen Siraj Mitwalli ,Co-Prof. Randa Ahmed Hariri 5. Education policy document in the Kingdom of Saudi Arabia in achieving sustainable development (Analytical study) Ms. Wafiah Othman Alsubhi ,Ms. Maha Saleh Saad Alyahyan ,Prof. Fatimah Abdallah Albeshr 6. The Reality of Using Artificial Intelligence Applications in Educating Students with Disabilities in the Sultanate of Oman from the Perspective of Their Teachers Dr. Khalid Saif Al-Maqrashi 7. Psychometric properties of the Social and Emotional Learning Scale: Social Skills Improvement System (SSIS SEL) Ms. Norah Abdulaziz Alquwaie, Prof. Mohammad Sulaiman Alwatban 8. Relationship between Sensory Learning, Recalling Styles and Speaking Proficiency: A Case Study of Yemeni EFL University Students Mr. Abdul-Rahim Ali Al-Showthabi, Prof. Mohammed Abdo Ahmed Al-Mekhlafi, Dr. Safiah Jobran Alghamri